THE USE OF ENGLISH IN FACEBOOK WALL (FBW) BY PRIMARY SCHOOL STUDENTS - Bin Masron, Muhammad Hafiz (International Journal of Psychosocial Rehabilitation, 2020)
The benefit and harm of social networking sites had been disputed among communicationists and educationists for years, but a solid conclusion was never surfaced. In rural Malaysia, social networking sites such as Facebook (FB) gradually embraced into the contemporary lesson system as one of the main approaches to support the students’ educational communications of written English language. Relevantly, many of the previous studies claimed that rural children frequently discovered with poor performance in the English language communications, in partcular of written form (Nor Shafiah, 2010). However, it is evident throughout the studies that most of the related assessment were conducted in school stuctured environment which highly triggered to the increase of anxiety level among the students subsequently led to the decrease of motivation toward written English communication (WEC). Furthermore, the connectedness of rural students to technology and the penetration to social network were proven to increase (Alias et al. 2010; Hazura et al., 2012), further helped the researcher to disclose interesting discovery of the current English usage for communication purposes among them. Therefore, this research aims to investigate the extent of written English for communication by FELDA primary school students through their interaction (posts and comments) on Facebook wall (FBW), followed by how far the communication is developed. Data for the study obtained from upper primary level students between 10 and 12 years. The collected data were further processed and transformed into several meaningful information based on the structured variables and objectives. The findings revealed that some of the unexpected results were drawn, further enhanced the existence of relationship between FB application (daily, weekly, monthly) and use of written English for communication among FELDA primary school students was absolutely undeniable. Ultimately, the students proposed their desire for the integration of FB application into formal English Lesson to make English communication more fun, effective, and motivating. The findings of the current study will definitely enrich the corpus of work conducted on the influence of social networking sites toward present children’s English language development and encourage further detailed research in this area.